Synovial tissue volume: a treatment target in knee osteoarthritis (OA). Issue 1 (26th June 2015) - O'Neill, Terence W; Parkes, Matthew J; Maricar, Nasimah; Marjanovic, Elizabeth J; Hodgson, Richard; Gait, Andrew D; Cootes, Timothy F; Hutchinson, Charles E; Felson, David T
Abstract : Background: Synovitis occurring frequently in osteoarthritis (OA) may be a targeted outcome. There are no data examining whether synovitis changes following intra-articular intervention. Methods: Persons aged 40 years and older with painful knee OA participated in an open label trial of intra-articular steroid therapy. At all time points they completed the Knee Injury and Osteoarthritis Outcome Score (KOOS) questionnaire. They had a contrast-enhanced (CE) MRI immediately prior to an intra-articular steroid injection with a repeat scan within 20 days. Response status was assessed using the Osteoarthritis Research Society International (OARSI) response criteria. OARSI responders were followed until their pain relapsed either within 20% of baseline or 6 months, shortly after which a third MRI was performed. Synovial tissue volume (STV) was measured on postcontrast knee images. We looked at changes in the STV and in pain, and their association. Results: 120 subjects with preinjection and postinjection CE MRI were followed. Their mean age was 62.3 years (SD=10.3) and 62 (52%) were women. The median time between injection and follow-up scan was 8 days (IQR 7–14 days). 85/120 (71%) were OARSI responders. Pain decreased (mean change in KOOS=+23.9; 95% CI 20.1 to 27.8, p<0.001) following steroid injection, as did mean STV (mean change=−1071 mm 3 ; 95% CI −1839 mm 3 to −303 mm 3, p=0.01). Of the 80 who returned for a third MRI, pain relapsed in 57, and in the 48 of those with MRI data, STV increased between follow-up and final visit (+1220 mm 3 ; 95% CI 25 mm 3 to 2414 mm 3, p=0.05). 23 were persistent responders at 6 months and, in these, STV did not increase (mean change=−202 mm 3 ; 95% CI −2008 mm 3 to 1604 mm 3, p=0.83). Controlling for variation over time, there was a significant association between synovitis volume and KOOS pain (b coefficient—change in KOOS pain score per 1000 mm 3 change in STV=−1.13; 95% CI −1.87 to −0.39, p=0.003), although STV accounted for only a small proportion of the variance in change in pain. Conclusions: Synovial tissue volume in knee OA shrinks following steroid therapy, and rebounds in those whose pain relapses. It can be considered a treatment target in symptomatic knee OA. Trial registration number: ISRCTN07329370.